Polishing liquid, polishing method, part manufacturing method, and semiconductor part manufacturing method

By using abrasive liquid composed of cerium oxide and halide ions in the abrasive liquid, the problem of low grinding speed of convex silicon oxide is solved, and high-efficiency grinding in pattern wafers and low-efficiency grinding in pattern wafers is achieved. Balance improves grinding efficiency and flatness.

CN119234296APending Publication Date: 2024-12-31RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095523.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the abrasive liquid containing cerium oxide abrasive particles, it is difficult to achieve a high grinding speed of the convex silicon oxide, especially in the grinding of patterned wafers with concave and convex patterns.

Method used

Using a grinding liquid containing cerium oxide, free aromatic carboxylic acid and its salts and halide ions, adsorbing halide ions on the surface of abrasive particles through halide ions, reducing electrostatic attraction, improving the binding activity of cerium oxide and silicon oxide, and enhancing grinding Effect.

Benefits of technology

A high grinding speed of the convex silicon oxide in the pattern wafer is achieved, while reducing the grinding speed of the silicon oxide in the patternless wafer is achieved, thereby improving the grinding efficiency and flatness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108207930000171
    Figure BDA0005108207930000171
  • Figure BDA0005108207930000231
    Figure BDA0005108207930000231
Patent Text Reader

Abstract

A polishing liquid containing: abrasive grains containing a cerium oxide; at least one aromatic carboxylic acid compound selected from the group consisting of aromatic carboxylic acids and salts thereof; and halide ions. Also provided is a polishing method in which a member to be polished is polished using the polishing liquid. Also provided is a method for manufacturing a component, in which a component is obtained using the member to be polished that has been polished by the polishing method. Also provided is a method for manufacturing a semiconductor component, in which a semiconductor component is obtained using a member to be polished that has been polished by the aforementioned polishing method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a grinding liquid, a grinding method, a method for manufacturing parts, a method for manufacturing semiconductor parts, etc. Background Art

[0002] In recent years, the importance of processing technologies for high density and miniaturization has been increasing in the manufacturing process of electronic devices. CMP (Chemical Mechanical Polishing) technology, one of the processing technologies, has become an essential technology in the manufacturing process of electronic devices for the formation of shallow trench isolation (STI), planarization of pre-metal insulating materials or interlayer insulating materials, and formation of plugs or embedded metal wiring. As a polishing liquid used for CMP, a polishing liquid containing abrasive grains containing cerium oxide is known (for example, refer to the following patent documents 1 and 2).

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 10-106994

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 08-022970 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] However, in polishing a pattern wafer having a concavo-convex pattern composed of convex portions and concave portions in a polishing liquid containing abrasive grains containing cerium oxide, it may be difficult to achieve a high polishing rate for silicon oxide in the convex portions.

[0009] One aspect of the present invention is to provide a polishing liquid that can achieve a high polishing rate of silicon oxide on a convex portion when polishing a pattern wafer having a concave-convex pattern. Another aspect of the present invention is to provide a polishing method, wherein the polishing liquid is used. Another aspect of the present invention is to provide a method for manufacturing a part, wherein the polishing method is used. Another aspect of the present invention is to provide a method for manufacturing a semiconductor part, wherein the polishing method is used.

[0010] Means for solving technical problems

[0011] The present invention relates in some aspects to the following [1] to

[19] and the like.

[0012] [1] A polishing liquid comprising: abrasive grains comprising cerium oxide; at least one aromatic carboxylic acid compound selected from the group consisting of aromatic carboxylic acids and salts thereof; and halide ions.

[0013] [2] The polishing liquid according to [1], wherein

[0014] The halide ion includes at least one selected from the group consisting of fluoride ion, chloride ion, bromide ion, and iodide ion.

[0015] [3] The polishing liquid according to [1], wherein

[0016] The halide ions include iodide ions.

[0017] [4] The polishing liquid according to any one of [1] to [3], wherein

[0018] The content of the halide ion is 0.01-5.0 mM.

[0019] [5] The polishing liquid according to any one of [1] to [4], wherein

[0020] The aromatic carboxylic acid compound includes at least one selected from the group consisting of benzoic acid and salts thereof.

[0021] [6] The polishing liquid according to any one of [1] to [5], wherein

[0022] The aromatic carboxylic acid compound includes at least one selected from the group consisting of mandelic acid and salts thereof.

[0023] [7] The polishing liquid according to any one of [1] to [6], wherein

[0024] The content of the aromatic carboxylic acid compound is 0.01 to 1% by mass.

[0025] [8] The polishing liquid according to any one of [1] to [7], further comprising an alkali metal ion.

[0026] [9] The polishing liquid according to any one of [1] to [8], further comprising a nitrogen-containing cation.

[0027]

[10] The polishing liquid according to [9], wherein

[0028] The nitrogen-containing cation includes at least one selected from the group consisting of ammonium ions and quaternary ammonium cations.

[0029]

[11] The polishing liquid according to any one of [1] to

[10] , wherein

[0030] The content of the abrasive grains is 0.1 to 5% by mass.

[0031]

[12] The polishing liquid according to any one of [1] to

[11] , wherein

[0032] The abrasive particles have a positive zeta potential.

[0033]

[13] The polishing liquid according to any one of [1] to

[12] , further comprising a cationic polymer.

[0034]

[14] The polishing liquid according to

[13] , wherein

[0035] The cationic polymer includes a reactant of raw materials including at least dimethylamine and epichlorohydrin.

[0036]

[15] The polishing liquid according to any one of [1] to

[14] , wherein the pH thereof is 2.00 to 5.00.

[0037]

[16] A grinding method, wherein:

[0038] The workpiece is polished using the polishing liquid described in any one of [1] to

[15] .

[0039]

[17] The grinding method according to

[16] , wherein:

[0040] The polished part includes silicon oxide.

[0041]

[18] A method for manufacturing a part, wherein:

[0042] A part is obtained by using a part to be ground by the grinding method described in

[16] or

[17] .

[0043]

[19] A method for manufacturing a semiconductor component, wherein:

[0044] A semiconductor component is obtained using the polished member polished by the polishing method described in

[16] or

[17] .

[0045] Effects of the Invention

[0046] According to one aspect of the present invention, a polishing liquid capable of achieving a high polishing rate of silicon oxide on a convex portion in the polishing of a pattern wafer having a concave-convex pattern can be provided. According to another aspect of the present invention, a polishing method can be provided, wherein the polishing liquid is used. According to another aspect of the present invention, a method for manufacturing a part can be provided, wherein the polishing method is used. According to another aspect of the present invention, a method for manufacturing a semiconductor part can be provided, wherein the polishing method is used. DETAILED DESCRIPTION

[0047] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0048] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. "Above A" in the numerical range refers to A and the range exceeding A. "Below A" in the numerical range refers to A and the range less than A. In the numerical range described in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" can include either A and B, or both. Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. Regarding the content of each component in the composition, when there are multiple substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. Regarding the term "film", in addition to the structure of the shape formed on the entire surface when observed in a top view, it also includes the structure of the shape formed in a part. The term "process" does not only include independent processes, but also includes processes that cannot be clearly distinguished from other processes as long as the desired effect of the process is achieved. Unless otherwise specified, "alkyl" may be linear, branched, or cyclic. "Abrasive" refers to a collection of multiple particles, but for convenience, one particle constituting abrasive is sometimes referred to as an abrasive.

[0049] <Polishing fluid>

[0050] The polishing liquid according to the present embodiment contains: abrasive grains containing cerium oxide; at least one aromatic carboxylic acid compound selected from the group consisting of aromatic carboxylic acids and salts thereof; and halide ions. The polishing liquid according to the present embodiment can be used as a CMP polishing liquid.

[0051] According to the polishing liquid involved in this embodiment, in the polishing of a pattern wafer having a concave-convex pattern composed of convex portions and concave portions, a high polishing rate of silicon oxide (e.g., silicon dioxide) on the convex portions can be achieved. For example, in the evaluation method described in the embodiments described later, the polishing rate of silicon oxide as the convex portions can be, for example, 2500nm / min or more (preferably 3000nm / min or more, 3500nm / min or more, 4000nm / min or more, 4500nm / min or more, 5000nm / min or more, etc.).

[0052] The reason why a high polishing rate of silicon oxide in the convex portion is obtained in polishing of a pattern wafer is not clear, but is presumed to be as follows. However, the main reason is not limited to the following.

[0053] That is, the halide ions are adsorbed on the surface of the abrasive grains containing cerium oxide, thereby easily forming active sites for generating the bonding between the cerium oxide of the abrasive grains and the silicon oxide of the polished part. On the other hand, the halide ions are adsorbed on the surface of the abrasive grains containing cerium oxide, thereby reducing the surface potential (zeta potential) of the abrasive grains and increasing the ion strength in the polishing liquid, so that the electrostatic attraction (interaction) between the abrasive grains and the silicon oxide of the polished part is easily reduced.

[0054] In the grinding of the convex part of the pattern wafer, the pressure applied is higher than that of the concave part, and a relatively high shear stress is applied, so it is easy to give abrasive grains a large mechanical energy. In this case, the above-mentioned active sites in the abrasive grains containing cerium oxide easily react with the silicon oxide of the polished part to form a bond between cerium oxide and silicon oxide (for example, Ce-O-Si), and it is easy to obtain a grinding promotion effect with a greater effect than the above-mentioned effect of reducing electrostatic attraction. Thus, a high grinding speed of silicon oxide in the convex part can be achieved in the grinding of the pattern wafer.

[0055] In the grinding of a pattern wafer having a concave-convex pattern composed of protrusions and concave portions, it is required to reduce the grinding speed of the concave portions in order to improve the flatness after grinding. Here, the smaller the density of the protrusions in the pattern wafer, the easier it is for the state of the concave portions to be close to the state of a plain wafer without a concave-convex pattern. Therefore, from the viewpoint of reducing the grinding speed of the concave portions in the pattern wafer having a small density of protrusions, it is required to reduce the grinding speed of the plain wafer. In contrast, according to one method of the grinding liquid involved in the present embodiment, the grinding speed of silicon oxide (e.g., silicon dioxide) can be reduced in the grinding of a plain wafer without a concave-convex pattern. For example, in the evaluation method described in the examples described later, as the grinding speed of silicon oxide, for example, The following (preferably the following, the following, the following, the following, the following, the following, the following, That is, according to one aspect of the polishing liquid according to the present embodiment, it is possible to reduce the polishing rate of silicon oxide in polishing a plain wafer and achieve a high polishing rate of silicon oxide in polishing a convex portion in polishing a patterned wafer.

[0056] The reason why the polishing rate of silicon oxide decreases during polishing of a matte wafer is not clear, but is presumed to be as follows. However, the main reason is not limited to the following.

[0057] That is, as described above, halide ions are adsorbed on the surface of the abrasive containing cerium oxide, thereby easily forming active sites for generating bonding between the cerium oxide of the abrasive and the silicon oxide of the polished part, but the electrostatic attraction (interaction) between the abrasive and the silicon oxide of the polished part is easily reduced.

[0058] In the polishing of a plain wafer, the pressure applied is lower than that of the convex part in a patterned wafer, and it is difficult to impart large mechanical energy to the abrasive grains. In this case, the reduction of the electrostatic attraction between the abrasive grains and the silicon oxide of the polished part is likely to have a greater impact, so it is difficult to overcome the activation barrier used to form a bond between cerium oxide and silicon oxide (e.g., Ce-O-Si), and it is difficult to obtain a polishing promotion effect. As a result, the polishing speed of silicon oxide is reduced in the polishing of a plain wafer.

[0059] The polishing liquid involved in this embodiment contains abrasive particles containing cerium oxide. By using abrasive particles containing cerium oxide, it is easy to obtain a high polishing rate of silicon oxide in the pattern wafer. Cerium oxide can be CeO2 (cerium (IV) oxide, ceria) or Ce2O3 (cerium (III) oxide). The abrasive particles can contain constituent materials other than cerium oxide. As constituent materials of abrasive particles other than cerium oxide, inorganic materials such as silicon dioxide (SiO2), aluminum oxide, zirconium oxide, titanium dioxide, germanium dioxide, and silicon carbide can be cited.

[0060] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the content of cerium oxide in the abrasive grains may be 90 mass % or more, 93 mass % or more, 95 mass % or more, more than 95 mass %, 98 mass % or more, 99 mass % or more, 99.5 mass % or more, or 99.9 mass % or more, based on the abrasive grains as a whole (the abrasive grains as a whole or the abrasive grains as a whole or the abrasive grains constituting one particle of the abrasive grains as a whole). The abrasive grains may be substantially formed of cerium oxide (substantially 100 mass % of the abrasive grains are in the form of cerium oxide).

[0061] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the Zeta potential (surface potential) of the abrasive in the polishing liquid can be positive (the Zeta potential can exceed 0 mV). The Zeta potential of the abrasive can be 1 mV or more, 5 mV or more, 10 mV or more, 15 mV or more, 20 mV or more, 21 mV or more, 22 mV or more, 23 mV or more, 24 mV or more, 24.5 mV or more, or 25 mV or more. The Zeta potential of the abrasive can be 100 mV or less, 80 mV or less, 60 mV or less, 50 mV or less, 40 mV or less, 35 mV or less, 30 mV or less, 28 mV or less, 26 mV or less, 25 mV or less, 24.5 mV or less, 24 mV or less, 23 mV or less, 22 mV or less, 21 mV or less, or 20 mV or less. From these viewpoints, the zeta potential of the abrasive can be more than 0 mV and less than 100 mV, more than 0 mV and less than 50 mV, more than 0 mV and less than 30 mV, 10 to 100 mV, 10 to 50 mV, 10 to 30 mV, 20 to 100 mV, 20 to 50 mV, or 20 to 30 mV. The zeta potential of the abrasive can be measured by the method described in the examples described below.

[0062] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in the pattern wafer, the average particle size of the abrasive grains may be 10 nm or more, 30 nm or more, 50 nm or more, 80 nm or more, 100 nm or more, more than 100 nm, 120 nm or more, 150 nm or more, 180 nm or more, 200 nm or more, 220 nm or more, 250 nm or more, 270 nm or more, or 280 nm or more. From the viewpoint of easily suppressing the generation of polishing scratches, the average particle size of the abrasive grains may be 1000 nm or less, 800 nm or less, 600 nm or less, 500 nm or less, 450 nm or less, 400 nm or less, 380 nm or less, 350 nm or less, 330 nm or less, 300 nm or less, or 280 nm or less. From these viewpoints, the average particle size of the abrasive grains may be 10 to 1000 nm, 10 to 600 nm, 10 to 400 nm, 100 to 1000 nm, 100 to 600 nm, 100 to 400 nm, 200 to 1000 nm, 200 to 600 nm or 200 to 400 nm. The average particle size of the abrasive grains can be measured by the method described in the Examples described below.

[0063] Based on the total mass of the polishing liquid, the content of the abrasive can be within the following range. From the perspective of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the content of the abrasive can be 0.01 mass % or more, 0.05 mass % or more, 0.1 mass % or more, 0.3 mass % or more, 0.5 mass % or more, more than 0.5 mass %, 0.7 mass % or more, 0.8 mass % or more, 0.9 mass % or more, or 1 mass % or more. From the perspective of easily suppressing the saturation of the increase in the polishing rate relative to the increase in the content of the abrasive, and from the perspective of easily suppressing the increase in the viscosity of the polishing liquid, the abrasive agglomeration, the increase in the cost of polishing, the generation of polishing scratches, etc., the content of the abrasive can be 10 mass % or less, 8 mass % or less, 5 mass % or less, 4 mass % or less, 3 mass % or less, 2 mass % or less, 1.5 mass % or less, or 1 mass % or less. From these viewpoints, the content of the abrasive grains may be 0.01 to 10 mass %, 0.1 to 10 mass %, 0.5 to 10 mass %, 0.01 to 5 mass %, 0.1 to 5 mass %, 0.5 to 5 mass %, 0.01 to 3 mass %, 0.1 to 3 mass % or 0.5 to 3 mass %.

[0064] The polishing liquid involved in this embodiment contains at least one aromatic carboxylic acid compound selected from the group consisting of aromatic carboxylic acids (aromatic compounds having a carboxyl group) and salts thereof. As salts of aromatic carboxylic acids, metal salts such as alkali metal salts can be cited. As alkali metal salts, sodium salts, potassium salts, etc. can be cited.

[0065] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in the pattern wafer, the total number of carboxyl groups and carboxylate groups in the aromatic carboxylic acid compound, the number of carboxyl groups in the aromatic carboxylic acid, or the number of carboxylate groups in the salt of the aromatic carboxylic acid may be 1-3 or 1-2.

[0066] As the aromatic ring of the aromatic carboxylic acid compound, a benzene ring, a naphthalene ring, an anthracene ring, a pyridine ring, a quinoline ring, etc. can be mentioned. From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the aromatic carboxylic acid compound may have a benzene ring. From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the number of aromatic rings or the number of benzene rings in the aromatic carboxylic acid compound may be 1 to 3 or 1 to 2. The aromatic carboxylic acid compound may include a compound having a heteroaromatic ring, and may also include a compound not having a heteroaromatic ring.

[0067] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a pattern wafer, the aromatic carboxylic acid compound may include at least one selected from the group consisting of aromatic hydroxy acids (aromatic hydroxycarboxylic acids) and salts thereof, or may include at least one selected from the group consisting of aromatic α-hydroxy acids and salts thereof.

[0068] Examples of the aromatic carboxylic acid include benzoic acid, benzoic acid derivatives, hydroxyphenylacetic acid, phthalic acid, phthalic acid derivatives, quinolinic acid, quinoline derivatives, and pyridinecarboxylic acid.

[0069] Examples of benzoic acid derivatives include compounds in which the hydrogen atoms of the benzene ring of benzoic acid are substituted with a substituent (alkyl, hydroxyl, amino, sulfo, etc.) different from the carboxyl group, and examples include hydroxybenzoic acid, aminobenzoic acid, alkyl salicylic acid, etc. Examples of hydroxybenzoic acid include salicylic acid (2-hydroxybenzoic acid) and 4-hydroxybenzoic acid. Examples of aminobenzoic acid include anthranilic acid, etc. Examples of alkyl salicylic acid include methyl salicylic acid (for example, 3-methyl salicylic acid), etc. Examples of hydroxyphenylacetic acid include mandelic acid (2-hydroxy-2-phenylacetic acid) and 4-hydroxyphenylacetic acid. Examples of phthalic acid derivatives include compounds in which the hydrogen atoms of the benzene ring of phthalic acid are substituted with a substituent (alkyl, hydroxyl, amino, sulfo, etc.) different from the carboxyl group, and examples include alkyl phthalic acid, aminophthalic acid, sulfophthalic acid, etc. As alkylphthalic acid, methylphthalic acid (e.g., 4-methylphthalic acid) etc. can be mentioned. As aminophthalic acid, 4-aminophthalic acid etc. can be mentioned. As sulfophthalic acid, 4-sulfophthalic acid etc. can be mentioned. As quinoline derivatives, compounds in which the hydrogen atom of the pyridine ring of quinolinic acid is substituted with a substituent (alkyl, hydroxyl, amino, sulfo, etc.) different from the carboxyl group can be mentioned, and quinolinecarboxylic acid etc. can be mentioned. As quinolinecarboxylic acid, quinaldic acid etc. can be mentioned. As pyridinecarboxylic acid, picolinic acid, nicotinic acid etc. can be mentioned.

[0070] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer, the aromatic carboxylic acid compound may include at least one selected from the group consisting of benzoic acid, benzoic acid derivatives, hydroxyphenylacetic acid and salts thereof, may include at least one selected from the group consisting of benzoic acid, mandelic acid, o-aminobenzoic acid and salts thereof, may include at least one selected from the group consisting of benzoic acid, mandelic acid and salts thereof, may include at least one selected from the group consisting of benzoic acid and its salts, and may include at least one selected from the group consisting of mandelic acid and its salts.

[0071] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the molecular weight of the aromatic carboxylic acid compound may be within the following range. The molecular weight of the aromatic carboxylic acid compound may be 80 or more, 90 or more, 100 or more, 110 or more, 120 or more, 125 or more, 130 or more, 140 or more, 145 or more, or 150 or more. The molecular weight of the aromatic carboxylic acid compound may be 1000 or less, less than 1000, 900 or less, 800 or less, 700 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, 180 or less, 170 or less, 160 or less, 150 or less, 145 or less, 140 or less, 135 or less, 130 or less, or 125 or less. From these viewpoints, the molecular weight of the aromatic carboxylic acid compound may be 80-1000, 80-300, 80-180, 100-1000, 100-300, 100-180, 120-1000, 120-300 or 120-180.

[0072] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the content of benzoic acid can be within the following ranges based on the total mass of the aromatic carboxylic acid compound (the total mass of the aromatic carboxylic acid compound contained in the polishing liquid involved in the present embodiment). The content of benzoic acid can be 30% by mass or more, 35% by mass or more, 40% by mass or more, 45% by mass or more, 50% by mass or more, more than 50% by mass, 55% by mass or more, 60% by mass or more, 65% by mass or more, or 70% by mass or more. The content of benzoic acid can be 100% by mass or less, less than 100% by mass, 95% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, or 75% by mass or less. From these viewpoints, the content of benzoic acid may be 30-100 mass %, 30-90 mass %, 30-80 mass %, 50-100 mass %, 50-90 mass %, 50-80 mass %, 60-100 mass %, 60-90 mass % or 60-80 mass %.

[0073] As the content of hydroxyphenylacetic acid or mandelic acid, from the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the total mass of the aromatic carboxylic acid compound (the total mass of the aromatic carboxylic acid compound contained in the polishing liquid involved in the present embodiment) is used as a reference, and the content A1 can be within the following range. The content A1 can exceed 0 mass%, 5 mass% or more, 10 mass% or more, 15 mass% or more, 20 mass% or more, or 25 mass% or more. The content A1 can be 70 mass% or less, 65 mass% or less, 60 mass% or less, 55 mass% or less, 50 mass% or less, less than 50 mass%, 45 mass% or less, 40 mass% or less, 35 mass% or less, or 30 mass% or less. From these viewpoints, the content A1 can be more than 0 mass % and 70 mass % or less, more than 0 mass % and 50 mass % or less, more than 0 mass % and 40 mass % or less, 10 to 70 mass %, 10 to 50 mass %, 10 to 40 mass %, 20 to 70 mass %, 20 to 50 mass % or 20 to 40 mass %.

[0074] As the content of hydroxyphenylacetic acid or the content of mandelic acid, from the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the content A2 can be within the following range based on the total mass of benzoic acid. The content A2 can be 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, or 35% by mass or more. The content A2 can be 80% by mass or less, 75% by mass or less, 70% by mass or less, 65% by mass or less, 60% by mass or less, 55% by mass or less, 50% by mass or less, less than 50% by mass, 45% by mass or less, or 40% by mass or less. From these viewpoints, the content A2 can be 5-80% by mass, 5-60% by mass, 5-40% by mass, 20-80% by mass, 20-60% by mass, 20-40% by mass, 30-80% by mass, 30-60% by mass, or 30-40% by mass.

[0075] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the content of the aromatic carboxylic acid compound can be within the following ranges based on the total mass of the polishing liquid. The content of the aromatic carboxylic acid compound can be 0.001 mass %, 0.005 mass %, 0.01 mass %, 0.03 mass %, 0.05 mass %, 0.06 mass %, 0.08 mass %, 0.1 mass %, more than 0.1 mass %, 0.12 mass %, 0.15 mass %, 0.16 mass %, 0.18 mass % or more or 0.2 mass %. The content of the aromatic carboxylic acid compound can be 10 mass % or less, 8 mass % or less, 5 mass % or less, 3 mass % or less, 2 mass % or less, 1 mass % or less, 0.8 mass %, 0.6 mass %, 0.5 mass %, 0.4 mass % or less or 0.3 mass %. From these viewpoints, the content of the aromatic carboxylic acid compound may be 0.001 to 10 mass %, 0.001 to 1 mass %, 0.001 to 0.5 mass %, 0.01 to 10 mass %, 0.01 to 1 mass %, 0.01 to 0.5 mass %, 0.1 to 10 mass %, 0.1 to 1 mass % or 0.1 to 0.5 mass %.

[0076] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the content of benzoic acid can be within the following ranges based on the total mass of the polishing liquid. The content of benzoic acid can be 0.001 mass %, 0.005 mass %, 0.01 mass %, 0.03 mass %, 0.05 mass %, 0.06 mass %, 0.08 mass %, 0.1 mass %, more than 0.1 mass %, 0.12 mass %, 0.15 mass % or more or 0.16 mass %. The content of benzoic acid can be 10 mass % or less, 8 mass % or less, 5 mass % or less, 3 mass % or less, 2 mass % or less, 1 mass % or less, 0.8 mass % or less, 0.6 mass % or less, 0.5 mass % or less, 0.4 mass % or less, 0.3 mass % or less, 0.2 mass % or less, 0.18 mass % or less or 0.16 mass % or less. From these viewpoints, the content of benzoic acid may be 0.001 to 10 mass %, 0.001 to 1 mass %, 0.001 to 0.5 mass %, 0.01 to 10 mass %, 0.01 to 1 mass %, 0.01 to 0.5 mass %, 0.1 to 10 mass %, 0.1 to 1 mass % or 0.1 to 0.5 mass %.

[0077] As the content of hydroxyphenylacetic acid or mandelic acid, from the viewpoint of easily obtaining a high polishing rate of silicon oxide in a pattern wafer, the content A3 can be within the following range based on the total mass of the polishing liquid. The content A3 can be 0.001 mass % or more, 0.005 mass % or more, 0.01 mass % or more, 0.03 mass % or more, 0.05 mass % or more, or 0.06 mass % or more. The content A3 can be 10 mass % or less, 8 mass % or less, 5 mass % or less, 3 mass % or less, 2 mass % or less, 1 mass % or less, 0.8 mass % or less, 0.6 mass % or less, 0.5 mass % or less, 0.4 mass % or less, 0.3 mass % or less, 0.2 mass % or less, 0.18 mass % or less, 0.16 mass % or less, 0.15 mass % or less, 0.12 mass % or less, 0.1 mass % or less, 0.08 mass % or less, or 0.06 mass % or less. From these viewpoints, the content A3 may be 0.001 to 10 mass %, 0.001 to 1 mass %, 0.001 to 0.5 mass %, 0.01 to 10 mass %, 0.01 to 1 mass %, 0.01 to 0.5 mass %, 0.05 to 10 mass %, 0.05 to 1 mass % or 0.05 to 0.5 mass %.

[0078] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the mass ratio A4 (aromatic carboxylic acid compound / abrasive) of the content of the aromatic carboxylic acid compound to the content of the abrasive grains may be within the following range. The mass ratio A4 may be 0.001 or more, 0.005 or more, 0.01 or more, 0.03 or more, 0.05 or more, 0.06 or more, 0.08 or more, 0.1 or more, 0.12 or more, 0.15 or more, 0.16 or more, 0.18 or more, or 0.2 or more. The mass ratio A4 may be 10 or less, 8 or less, 5 or less, 3 or less, 2 or less, 1 or less, less than 1, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. From these viewpoints, the mass ratio A4 may be 0.001 to 10, 0.001 to 1, 0.001 to 0.5, 0.01 to 10, 0.01 to 1, 0.01 to 0.5, 0.1 to 10, 0.1 to 1 or 0.1 to 0.5.

[0079] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the mass ratio A5 (benzoic acid / abrasive) of the content of benzoic acid to the content of abrasive grains may be within the following range. The mass ratio A5 may be 0.001 or more, 0.005 or more, 0.01 or more, 0.03 or more, 0.05 or more, 0.06 or more, 0.08 or more, 0.1 or more, 0.12 or more, 0.15 or more, or 0.16 or more. The mass ratio A5 may be 10 or less, 8 or less, 5 or less, 3 or less, 2 or less, 1 or less, less than 1, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.18 or less, or 0.16 or less. From these viewpoints, the mass ratio A5 may be 0.001 to 10, 0.001 to 1, 0.001 to 0.5, 0.01 to 10, 0.01 to 1, 0.01 to 0.5, 0.1 to 10, 0.1 to 1 or 0.1 to 0.5.

[0080] As the mass ratio of the content of hydroxyphenylacetic acid to the content of abrasive (hydroxyphenylacetic acid / abrasive) or the mass ratio of the content of mandelic acid to the content of abrasive (mandelic acid / abrasive), from the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the mass ratio A6 may be within the following range. The mass ratio A6 may be 0.001 or more, 0.005 or more, 0.01 or more, 0.03 or more, 0.05 or more, or 0.06 or more. The mass ratio A6 may be 10 or less, 8 or less, 5 or less, 3 or less, 2 or less, 1 or less, less than 1, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.18 or less, 0.16 or less, 0.15 or less, 0.12 or less, 0.1 or less, 0.08 or less, or 0.06 or less. From these viewpoints, the mass ratio A6 may be 0.001 to 10, 0.001 to 1, 0.001 to 0.5, 0.01 to 10, 0.01 to 1, 0.01 to 0.5, 0.05 to 10, 0.05 to 1 or 0.05 to 0.5.

[0081] The polishing liquid according to the present embodiment contains halide ions. In the polishing liquid according to the present embodiment, the halide ions may be bonded to counter cations or may be free without being bonded to counter cations. As counter cations, cations described below may be used.

[0082] As halide ions, fluoride ions, chloride ions, bromide ions, iodide ions, etc. can be cited. From the viewpoint of easily obtaining a high polishing speed of silicon oxide in a patterned wafer and easily reducing the polishing speed of silicon oxide in a non-patterned wafer, the halide ions may include at least one selected from the group consisting of fluoride ions, chloride ions, bromide ions, and iodide ions. From the viewpoint of easily obtaining a high polishing speed of silicon oxide in a patterned wafer, the halide ions may include at least one selected from the group consisting of fluoride ions, chloride ions, and iodide ions, may include at least one selected from the group consisting of fluoride ions and iodide ions, and may also include iodide ions. From the viewpoint of easily reducing the polishing speed of silicon oxide in a non-patterned wafer, the halide ions may include at least one selected from the group consisting of chloride ions, bromide ions, and iodide ions, may include at least one selected from the group consisting of bromide ions and iodide ions, and may also include iodide ions.

[0083] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a patterned wafer and easily reducing the polishing rate of silicon oxide in a non-patterned wafer, the content of halide ions can be within the following ranges based on the total amount of the polishing liquid. The content of halide ions can be 0.01 mM or more, 0.05 mM or more, 0.10 mM or more, 0.20 mM or more, 0.30 mM or more, 0.40 mM or more, 0.45 mM or more, 0.50 mM or more, 0.55 mM or more, 0.60 mM or more, 0.65 mM or more, or 0.69 mM or more. The content of halide ions can be 5.0 mM or less, 3.0 mM or less, 1.0 mM or less, 0.90 mM or less, 0.80 mM or less, 0.75 mM or less, 0.70 mM or less, 0.69 mM or less, 0.65 mM or less, or 0.60 mM or less. From these viewpoints, the content of halide ions may be 0.01 to 5.0 mM, 0.01 to 3.0 mM, 0.01 to 1.0 mM, 0.10 to 5.0 mM, 0.10 to 3.0 mM, 0.10 to 1.0 mM, 0.30 to 5.0 mM, 0.30 to 3.0 mM or 0.30 to 1.0 mM.

[0084] The polishing liquid according to the present embodiment may contain a salt containing a halide ion. The salt containing a halide ion is a salt containing a halide ion and a counter cation, and as the counter cation, a cation described below can be used.

[0085] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and from the viewpoint of easily reducing the polishing rate for silicon oxide in a non-patterned wafer, the content of the salt containing halide ions may be within the following ranges based on the total mass of the polishing liquid. The content of the salt containing halide ions may be 0.001 mass % or more, 0.002 mass % or more, 0.003 mass % or more, 0.004 mass % or more, 0.005 mass % or more, 0.006 mass % or more, 0.007 mass % or more, 0.008 mass % or more, 0.009 mass % or more, 0.01 mass % or more, 0.012 mass % or more, 0.015 mass % or more, 0.02 mass % or more, or 0.025 mass % or more. The content of the salt containing halide ions may be 1 mass % or less, 0.5 mass % or less, 0.1 mass % or less, 0.05 mass % or less, 0.03 mass % or less, 0.025 mass % or less, 0.02 mass % or less, 0.015 mass % or less, 0.012 mass % or less, 0.01 mass % or less, 0.009 mass % or less, 0.008 mass % or less, 0.007 mass % or less, 0.006 mass % or less, 0.005 mass % or less, 0.004 mass % or less, or 0.003 mass % or less. From these viewpoints, the content of the salt containing halide ions may be 0.001 to 1 mass %, 0.001 to 0.1 mass %, 0.001 to 0.03 mass %, 0.005 to 1 mass %, 0.005 to 0.1 mass %, 0.005 to 0.03 mass %, 0.008 to 1 mass %, 0.008 to 0.1 mass % or 0.008 to 0.03 mass %.

[0086] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and from the viewpoint of easily reducing the polishing rate for silicon oxide in a non-patterned wafer, the mass ratio B1 of the content of the salt containing halide ions to the content of the abrasive (salt containing halide ions / abrasive) may be within the following range. The mass ratio B1 may be 0.001 or more, 0.002 or more, 0.003 or more, 0.004 or more, 0.005 or more, 0.006 or more, 0.007 or more, 0.008 or more, 0.009 or more, 0.01 or more, 0.012 or more, 0.015 or more, 0.02 or more, or 0.025 or more. The mass ratio B1 may be 1 or less, less than 1, 0.5 or less, 0.1 or less, 0.05 or less, 0.03 or less, 0.025 or less, 0.02 or less, 0.015 or less, 0.012 or less, 0.01 or less, 0.009 or less, 0.008 or less, 0.007 or less, 0.006 or less, 0.005 or less, 0.004 or less, or 0.003 or less. From these viewpoints, the mass ratio B1 may be 0.001 to 1, 0.001 to 0.1, 0.001 to 0.03, 0.005 to 1, 0.005 to 0.1, 0.005 to 0.03, 0.008 to 1, 0.008 to 0.1, or 0.008 to 0.03.

[0087] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a patterned wafer and easily reducing the polishing rate of silicon oxide in a non-patterned wafer, the mass ratio B2 (salt containing halide ions / aromatic carboxylic acid compound) of the content of the salt containing halide ions relative to the content of the aromatic carboxylic acid compound can be within the following range. The mass ratio B2 can be 0.001 or more, 0.005 or more, 0.01 or more, 0.015 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.08 or more, or 0.1 or more. The mass ratio B2 can be 1 or less, less than 1, 0.5 or less, 0.2 or less, 0.1 or less, 0.08 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.015 or less. From these viewpoints, the mass ratio B2 may be 0.001 to 1, 0.001 to 0.5, 0.001 to 0.2, 0.005 to 1, 0.005 to 0.5, 0.005 to 0.2, 0.015 to 1, 0.015 to 0.5, or 0.015 to 0.2.

[0088] The polishing liquid according to the present embodiment may contain cations. In the polishing liquid according to the present embodiment, the cations may be bonded to the counter anions or may be free without being bonded to the counter anions.

[0089] Examples of cations include metal ions (e.g., alkali metal ions), nitrogen-containing cations, etc. The polishing liquid involved in this embodiment may be in a form containing metal ions, in a form containing alkali metal ions, or in a form containing nitrogen-containing cations. The cation may be a counter cation in the salt of the aromatic carboxylic acid, or in a counter cation to the halide ion.

[0090] Examples of the alkali metal ions include sodium ions, potassium ions, etc. From the viewpoint of easily obtaining a high polishing rate for silicon oxide in the pattern wafer, the alkali metal ions may include at least one selected from the group consisting of sodium ions and potassium ions, and may include potassium ions.

[0091] Examples of nitrogen-containing cations include ammonium ions (NH4 + ), primary ammonium cations, secondary ammonium cations, tertiary ammonium cations, quaternary ammonium cations, imidazolium cations, pyridinium cations, pyrrolidinium cations, guanidinium cations, etc. From the perspective of easily obtaining a high polishing rate for silicon oxide in a patterned wafer, the nitrogen-containing cation may include at least one selected from the group consisting of ammonium ions, primary ammonium cations, secondary ammonium cations, tertiary ammonium cations, and quaternary ammonium cations, and may also include at least one selected from the group consisting of ammonium ions and quaternary ammonium cations.

[0092] In the quaternary ammonium cation, the number of alkyl groups bonded to the nitrogen atom or the number of unsubstituted alkyl groups bonded to the nitrogen atom may be 1-4, 2-4 or 3-4 from the viewpoint of easily obtaining a high polishing rate for silicon oxide in the pattern wafer.

[0093] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in the pattern wafer, the quaternary ammonium cation may have an alkyl group having the following carbon number as the alkyl group bonded to the nitrogen atom or the unsubstituted alkyl group bonded to the nitrogen atom. The number of carbon atoms of the alkyl group may be 1 or more, 2 or more, 3 or more, or 4 or more. The number of carbon atoms of the alkyl group may be 12 or less, 10 or less, 8 or less, 6 or less, or 4 or less. From these viewpoints, the number of carbon atoms of the alkyl group may be 1 to 12, 1 to 8, 1 to 4, 2 to 12, 2 to 8, 2 to 4, 3 to 12, 3 to 8, or 3 to 4.

[0094] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in the pattern wafer, the quaternary ammonium cation may include a tetraalkylammonium cation or may include at least one selected from the group consisting of a tetramethylammonium cation, a tetraethylammonium cation, a tetrapropylammonium cation and a tetrabutylammonium cation.

[0095] From the perspective of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and easily reducing the polishing rate for silicon oxide in a non-patterned wafer, the polishing liquid involved in this embodiment may contain at least one selected from the group consisting of potassium iodide, ammonium iodide, tetraalkylammonium iodide (for example, tetrabutylammonium iodide), ammonium bromide, ammonium chloride and ammonium fluoride as a salt containing halide ions and counter cations.

[0096] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and easily reducing the polishing rate for silicon oxide in a blank wafer, the polishing liquid according to this embodiment may contain a nonionic polymer (except the compound corresponding to the aromatic carboxylic acid compound). Examples of the nonionic polymer include polyglycerol, polyglycerol fatty acid ester, polyoxyethylene distyrenated phenyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene lauryl ether, polyoxypropylene polyoxyethylene alkyl ether, polyoxyethylene alkyl allyl ether, polyoxyethylene polyoxypropylene ether derivative, polyoxypropylene glycerol ether, polyethylene glycol, methoxypolyethylene glycol, ethylene glycol oxyethylene adducts, and other ether surfactants; sorbitan fatty acid ester, glycerol borate fatty acid ester, and other ester surfactants; polyoxyethylene alkylamine and other aminoether surfactants; polyoxyethylene glycerol borate fatty acid ester, polyoxyethylene alkyl ester and other ether ester surfactants; fatty acid alkanolamide, polyoxyethylene fatty acid alkanolamide and other alkanolamide surfactants; polyvinyl pyrrolidone; nonionic polyacrylamide; nonionic polydimethylacrylamide, etc. From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and easily reducing the polishing rate for silicon oxide in a non-patterned wafer, the nonionic polymer may include an ether surfactant or polyglycerol.

[0097] From the viewpoint of easily obtaining a high polishing rate for silicon oxide in a patterned wafer and from the viewpoint of easily reducing the polishing rate for silicon oxide in a non-patterned wafer, the molecular weight of the nonionic polymer or the molecular weight of the polyglycerol may be within the following ranges. The molecular weight may be 100 or more, 200 or more, 300 or more, 350 or more, 400 or more, 450 or more, 500 or more, 550 or more, 600 or more, 650 or more, 700 or more, or 750 or more. The molecular weight may be 5000 or less, 4000 or less, 3000 or less, 2000 or less, 1500 or less, 1200 or less, 1000 or less, 900 or less, 800 or less, or 750 or less. From these viewpoints, the molecular weight may be 100 to 5000, 100 to 3000, 100 to 1000, 300 to 5000, 300 to 3000, 300 to 1000, 500 to 5000, 500 to 3000 or 500 to 1000. The molecular weight may be, for example, a weight average molecular weight. For example, the weight average molecular weight can be obtained by measuring by gel permeation chromatography (GPC) under the following conditions and performing polyethylene glycol / polyethylene oxide conversion.

[0098] Equipment used (detector): "RID-10A" manufactured by SHIMADZU CORPORATION, differential refractometer for liquid chromatography

[0099] Pump: Made by SHIMADZU CORPORATION, "RID-10A"

[0100] Degassing device: Made by SHIMADZU CORPORATION, "DGU-20A3R"

[0101] Data processing: Manufactured by SHIMADZU CORPORATION, "LC solution"

[0102] Column: SHOWA DENKO MATERIALS CO., LTD., "Gelpak GL-W530 + Gelpak GL-W540", inner diameter 10.7 mm × 300 mm

[0103] Dissolution solution: 50 mM Na2HPO4 aqueous solution / acetonitrile = 90 / 10 (v / v)

[0104] Measurement temperature: 40℃

[0105] Flow rate: 1.0mL / min

[0106] Measurement time: 60 minutes

[0107] Sample: A solution having the same composition as the eluate was adjusted to a resin component concentration of 0.2 mass %, and filtered through a 0.45 μm membrane filter to prepare a sample.

[0108] Injection volume: 100 μL

[0109] Standard material: Polyethylene glycol / polyethylene oxide manufactured by TOSOH CORPORATION

[0110] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a patterned wafer and easily reducing the polishing rate of silicon oxide in a non-patterned wafer, the content of the nonionic polymer can be within the following range based on the total mass of the polishing liquid. The content of the nonionic polymer can be 0.01 mass % or more, 0.05 mass % or more, 0.1 mass % or more, 0.15 mass % or more, or 0.2 mass % or more. The content of the nonionic polymer can be 5 mass % or less, 3 mass % or less, 1 mass % or less, 0.5 mass % or less, 0.3 mass % or less, or 0.2 mass % or less. From these viewpoints, the content of the nonionic polymer can be 0.01 to 5 mass %, 0.01 to 1 mass %, 0.01 to 0.5 mass %, 0.05 to 5 mass %, 0.05 to 1 mass %, 0.05 to 0.5 mass %, 0.1 to 5 mass %, 0.1 to 1 mass % or 0.1 to 0.5 mass %.

[0111] From the viewpoint of easily reducing the polishing rate of silicon oxide in the matte wafer, the polishing liquid according to the present embodiment may contain a cationic polymer (except for the compound corresponding to the aromatic carboxylic acid compound). The cationic polymer has a cationic monomer as a monomer unit. Examples of the cationic monomer include ethyleneimine, allylamine, dimethyl(meth)acrylamide, diallylamine, methyldiallylamine, (meth)acrylic acid, diallyldimethylammonium chloride, (meth)acrylamide, dimethylamine, epichlorohydrin, ammonia, dimethylaminoethyl(meth)acrylate, dicyandiamide, diethylenetriamine, 3-(meth)acrylamidopropylmethyltrimethylammonium chloride, 3-(meth)acrylamidopropylmethyltrimethylammonium sulfide, 2-((meth)acryloyloxy)ethylmethyltrimethylammonium sulfide, 2-((meth)acryloyloxy)ethylmethyltrimethylammonium sulfide, vinylpyrrolidone-dimethylaminoethyl(meth)acrylate diethyl sulfate, diallyldimethylammonium chloride-(meth)acrylamide, and diallylmethylethylethylammonium sulfate.

[0112] From the viewpoint of easily reducing the polishing speed of silicon oxide in a patternless wafer, the cationic polymer may include a reactant (e.g., a condensate) of a raw material containing at least dimethylamine and epichlorohydrin, or may include a reactant (e.g., a condensate) of a raw material containing at least dimethylamine, ammonia, and epichlorohydrin. The raw material given to the reactant may include a compound other than dimethylamine, ammonia, and epichlorohydrin. From the viewpoint of easily reducing the polishing speed of silicon oxide in a patternless wafer, the cationic polymer may include a compound having a structure represented by the following formula. From the viewpoint of easily reducing the polishing speed of silicon oxide in a patternless wafer, the cationic polymer may include at least one selected from the group consisting of a dimethylamine / epichlorohydrin condensate (polycondensate) and a dimethylamine / ammonia / epichlorohydrin condensate (polycondensate).

[0113]

[0114] [In the formula, a represents an integer greater than or equal to 1, and b represents an integer greater than or equal to 0 (e.g., greater than or equal to 1).]

[0115] From the viewpoint of easily reducing the polishing speed of silicon oxide in the non-patterned wafer, the content of the cationic polymer can be within the following ranges based on the total mass of the polishing liquid. The content of the cationic polymer can be 0.0001 mass % or more, 0.0003 mass % or more, 0.0005 mass % or more, 0.0008 mass % or more, 0.001 mass % or more, 0.0012 mass % or more, or 0.0015 mass % or more. The content of the cationic polymer can be 0.1 mass % or less, 0.05 mass % or less, 0.01 mass % or less, 0.005 mass % or less, 0.003 mass % or less, or 0.002 mass % or less. From these viewpoints, the content of the cationic polymer may be 0.0001 to 0.1 mass %, 0.0001 to 0.01 mass %, 0.0001 to 0.005 mass %, 0.0005 to 0.1 mass %, 0.0005 to 0.01 mass %, 0.0005 to 0.005 mass %, 0.001 to 0.1 mass %, 0.001 to 0.01 mass % or 0.001 to 0.005 mass %.

[0116] The polishing liquid according to the present embodiment may contain water. Water may be contained as a remainder after removing other components from the polishing liquid.

[0117] The polishing liquid involved in this embodiment may contain components other than the above components. As such components, acid components, organic solvents, preservatives, alkaline hydroxides, peroxides, etc. can be cited. The polishing liquid involved in this embodiment may not contain at least one of these components. The polishing liquid involved in this embodiment may not contain at least one selected from the group consisting of starch and cyclodextrin.

[0118] From the viewpoint of easily obtaining a high polishing rate of silicon oxide in a patterned wafer and easily reducing the polishing rate of silicon oxide in a non-patterned wafer, the pH of the polishing liquid involved in the present embodiment can be within the following range. The pH of the polishing liquid can be 1.00 or more, more than 1.00, 1.50 or more, more than 1.50, 2.00 or more, more than 2.00, 2.20 or more, 2.50 or more, more than 2.50, 2.60 or more, 2.80 or more, 3.00 or more or more than 3.00. The pH of the polishing liquid can be 7.00 or less, less than 7.00, 6.50 or less, 6.00 or less, less than 6.00, 5.50 or less, 5.00 or less, less than 5.00, 4.50 or less, 4.00 or less, less than 4.00, 3.80 or less, 3.50 or less, 3.30 or less, 3.20 or less, 3.10 or less, 3.00 or less or less than 3.00. From these viewpoints, the pH of the polishing liquid may be 1.00 to 7.00, 1.00 to 5.00, 1.00 to 3.50, 2.00 to 7.00, 2.00 to 5.00, 2.00 to 3.50, 2.50 to 7.00, 2.50 to 5.00 or 2.50 to 3.50. The pH of the polishing liquid can be measured by the method described in the Examples below.

[0119] The polishing liquid involved in this embodiment can be stored as a polishing liquid storage liquid with less water than when used. The polishing liquid storage liquid is a storage liquid for obtaining a polishing liquid, and the polishing liquid is obtained by diluting the polishing liquid storage liquid with water before or during use. The dilution ratio is, for example, 1.5 times or more.

[0120] The polishing liquid involved in this embodiment can be stored as a single-liquid polishing liquid containing at least abrasive grains, aromatic carboxylic acid compounds and halide ions, and can also be stored as a multi-liquid polishing liquid having a slurry (first liquid) and an additive liquid (second liquid). In the multi-liquid polishing liquid, the constituent components of the polishing liquid are divided into a slurry and an additive liquid, so that the slurry and the additive liquid are mixed to form a polishing liquid. For example, the multi-liquid polishing liquid can be a slurry containing at least abrasive grains and water, the additive liquid contains at least an aromatic carboxylic acid compound and water, and the halide ions are contained in at least one form selected from the group consisting of the slurry and the additive liquid. The constituent components of the polishing liquid can be stored in three or more liquids. In the multi-liquid polishing liquid, the slurry and the additive liquid can be mixed before or during polishing to prepare the polishing liquid. The slurry and the additive liquid in the multi-liquid polishing liquid can be supplied to the polishing platform respectively, and the slurry and the additive liquid can be mixed on the polishing platform to prepare the polishing liquid.

[0121] <Grinding method>

[0122] The grinding method involved in the present embodiment includes a grinding process of grinding the part to be ground using the grinding liquid involved in the present embodiment. In the grinding process, the grinding surface of the part to be ground can be ground. In the grinding process, at least a portion of the part to be ground can be ground to remove. The part to be ground can contain silicon oxide (e.g., silicon dioxide). The grinding liquid used in the grinding process can be the above-mentioned single-liquid grinding liquid, can be a grinding liquid obtained by diluting the above-mentioned grinding liquid storage liquid with water, or can be a grinding liquid obtained by mixing the slurry and additive liquid in the above-mentioned multi-liquid grinding liquid. The part to be ground is not particularly limited, and can be a wafer (e.g., a semiconductor wafer) or a chip (e.g., a semiconductor chip). The part to be ground can be a circuit board or a circuit substrate.

[0123] <Manufacturing method, etc.>

[0124] The manufacturing method of the part involved in the present embodiment includes a part manufacturing process of obtaining a part by using a part to be ground (substrate) ground by the grinding method involved in the present embodiment. The part involved in the present embodiment is a part obtained by the manufacturing method of the part involved in the present embodiment. The part involved in the present embodiment is not particularly limited, but can be an electronic part (such as a semiconductor part such as a semiconductor package), a wafer (such as a semiconductor wafer), or a chip (such as a semiconductor chip). As one mode of the manufacturing method of the part involved in the present embodiment, in the manufacturing method of the electronic part involved in the present embodiment, an electronic part is obtained by using a part to be ground by the grinding method involved in the present embodiment. As one mode of the manufacturing method of the part involved in the present embodiment, in the manufacturing method of the semiconductor part involved in the present embodiment, a semiconductor part (such as a semiconductor package) is obtained by using a part to be ground by the grinding method involved in the present embodiment. The manufacturing method of the part involved in the present embodiment may include a grinding process of grinding the part to be ground by the grinding method involved in the present embodiment before the part manufacturing process.

[0125] In the manufacturing method of the part involved in the present embodiment, as one mode of the part manufacturing process, a singulation process of singulating the part to be ground (substrate) ground by the grinding method involved in the present embodiment may be included. The singulation process may be, for example, a process of cutting a wafer (such as a semiconductor wafer) ground by the grinding method involved in the present embodiment to obtain a chip (such as a semiconductor chip). As one mode of the manufacturing method of the part involved in the present embodiment, the manufacturing method of the electronic part involved in the present embodiment may include a process of obtaining an electronic part (such as a semiconductor part) by singulating the part to be ground using the grinding method involved in the present embodiment. As one mode of the manufacturing method of the part involved in the present embodiment, the manufacturing method of the semiconductor part involved in the present embodiment may include a process of obtaining a semiconductor part (such as a semiconductor package) by singulating the part to be ground using the grinding method involved in the present embodiment.

[0126] In the manufacturing method of the part involved in the present embodiment, as one mode of the part manufacturing process, a connection process of connecting (for example, electrically connecting) the part to be ground (substrate) ground by the grinding method involved in the present embodiment and other connected bodies can be included. The connected body connected to the part to be ground by the grinding method involved in the present embodiment is not particularly limited, and can be the part to be ground by the grinding method involved in the present embodiment, or can be a connected body different from the part to be ground by the grinding method involved in the present embodiment. In the connection process, the part to be ground and the connected body can be directly connected (connected in a state where the part to be ground and the connected body are in contact), or the part to be ground and the connected body can be connected via other components (conductive components, etc.). The connection process can be performed before the singulation process, after the singulation process, or before and after the singulation process.

[0127] The connecting process may be a process of connecting the polished surface of the polished component polished by the polishing method involved in the present embodiment and the connected body, or may be a process of connecting the connecting surface of the polished component polished by the polishing method involved in the present embodiment and the connecting surface of the connected body. The connecting surface of the polished component may be the polished surface polished by the polishing method involved in the present embodiment. Through the connecting process, a connected body having a polished component and a connected body can be obtained. In the connecting process, when the connecting surface of the polished component has a metal part, the connected body can be brought into contact with the metal part. In the connecting process, when the connecting surface of the polished component has a metal part and the connecting surface of the connected body has a metal part, the metal parts can be brought into contact with each other. The metal part may contain copper.

[0128] A device according to the present embodiment (for example, an electronic device such as a semiconductor device) includes at least one selected from the group consisting of a member to be polished by the polishing method according to the present embodiment and the component according to the present embodiment.

[0129] Example

[0130] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0131] <Production of cerium dioxide powder>

[0132] 40 kg of cerium carbonate hydrate was divided into 10 aluminum containers and calcined at 830°C in air for 2 hours to obtain a total of 20 kg of yellow-white powder. The powder was phase identified by X-ray diffraction, and it was confirmed that the powder contained polycrystalline cerium dioxide. The particle size of the powder obtained by calcination was observed by SEM, and it was found to be in the range of 20 to 100 μm. Next, 20 kg of cerium dioxide was dry-pulverized using a jet mill to obtain cerium dioxide powder. The specific surface area of ​​the pulverized cerium dioxide powder is 9.4 m 2 / g. The specific surface area was measured by the BET method.

[0133] <Preparation of slurry>

[0134] 15.0kg of the above-mentioned ceria powder and 84.5kg of deionized water were placed in a container and mixed. Then, 0.5kg of 1M (mol / L, about 6% by mass) acetic acid was added and stirred for 10 minutes to obtain a ceria mixed solution. The ceria mixed solution was sent to another container over 30 minutes. During this period, the ceria mixed solution was irradiated with ultrasonic waves at an ultrasonic frequency of 400kHz in the piping for sending the solution.

[0135] The ceria mixed solution of liquid feeding by ultrasonic irradiation was loaded into 4 1000m L polyethylene containers with 800g ± 8g respectively. Under the condition that the centrifugal force applied to the periphery becomes 500G, the ceria mixed solution in each container was centrifuged for 20 minutes. After centrifugation, the supernatant component of the container was collected to obtain slurry. The slurry contains about 10.0% by mass of ceria particles (abrasive grains) based on the gross mass of the slurry.

[0136] <Preparation of polishing liquid>

[0137] The polishing liquid was prepared by mixing the components shown in Table 1 according to the following steps. First, the components other than water (ultrapure water) were placed in a container. Then, water (ultrapure water) was injected into the container and stirred to dissolve the components. Then, the slurry of the above-mentioned abrasive (cerium dioxide particles) was mixed in the container and stirred to obtain a polishing liquid. The content of each component (solid content) based on the total mass of the polishing liquid and the content of halide ions based on the total amount of the polishing liquid are shown in Table 1. The remainder of the polishing liquid after removing the components in Table 1 is water.

[0138] As the components shown in Table 1, the following components were used.

[0139] Aromatic carboxylic acid A: Benzoic acid

[0140] Aromatic carboxylic acid B: Mandelic acid

[0141] Iodide Salt A: Potassium Iodide

[0142] Iodide salt B: ammonium iodide

[0143] Iodide Salt C: Tetrabutylammonium iodide

[0144] Bromide salts: ammonium bromide

[0145] Chloride salts: ammonium chloride

[0146] Fluoride salt: ammonium fluoride

[0147] Nitrates: ammonium nitrate

[0148] Polyglycerol: manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., product name "PGL#750", weight average molecular weight 750

[0149] Cationic polymer: Dimethylamine / ammonia / epichlorohydrin polycondensate, manufactured by SENKA Corporation, product name "UNISENSE KHE105L"

[0150] <Measurement of average particle size>

[0151] The average particle size of the abrasive particles in the polishing liquid was measured using a laser diffraction / scattering particle size distribution analyzer (manufactured by Microtrac BEL Corp., product name: Microtrac MT3300EXII). As a result, the average particle size in each polishing liquid was 280 nm.

[0152] <Measurement of Zeta Potential>

[0153] The zeta potential of the abrasive grains in the polishing liquid of the example was measured using a zeta potential measuring device (product name: DELSANANOC manufactured by Beckman Instruments, Inc.). In the zeta potential measuring device, the scattering intensity of the sample to be measured was set to 1.0×10 4 ~5.0×10 4 The polishing liquid was diluted with water in the cps method to obtain a sample. Then, the sample was placed in a cell for measuring zeta potential and the zeta potential was measured. The results are shown in Table 1.

[0154] <Measurement of pH>

[0155] The pH of the polishing liquid was measured under the following conditions. The results are shown in Table 1.

[0156] Measurement temperature: 25±5℃

[0157] Measuring device: HORIBA, Ltd., product name: Model (D-71)

[0158] Determination method: After calibrating the 3-point pH meter using phthalate pH standard solution (pH 4.01), neutral phosphate pH standard solution (pH 6.86) and borate pH standard solution (pH 9.18) as pH standard solutions, the electrode of the pH meter was placed in the grinding liquid and the value was measured after it had stabilized for more than 2 minutes.

[0159] <Grinding evaluation>

[0160] As substrates (polished members) used for polishing evaluation, the following patterned wafers (PTW) and blank wafers (BKW) were prepared.

[0161] A 2 cm square pattern wafer (PTW) having a silicon oxide film having 21 linear protrusions of 12 mm in length, 30 μm in width, and 4.5 to 6.0 μm in height arranged in parallel at intervals of 570 μm in the center of the surface was prepared.

[0162] A laminated body including a 2 μm-thick silicon oxide film formed on a silicon substrate by CVD was cut into 2 cm squares to produce a blank wafer (BKW) having no pattern.

[0163] The substrate was fixed to a support with a substrate mounting adsorption pad of a polishing device (manufactured by NANOFACTOR Co., Ltd., product name: FACT-200) attached. The silicon oxide film of the substrate was placed on a platform with a foamed polyurethane polishing cloth attached, and the support was placed with the silicon oxide film of the substrate facing downward. 2 The weights were placed. The platform speed was set to 120 min. -1 , the above-mentioned polishing liquid was dripped onto the platform at 5 mL / min and the substrate was polished. The polishing time of the patterned wafer was 60 seconds, and the polishing time of the non-patterned wafer was 180 seconds. In the comparative example, the patterned wafer was polished, but the non-patterned wafer was not polished. The polishing speed was calculated based on the difference in film thickness obtained by measuring the film thickness of the silicon oxide film before and after polishing using an optical interference film thickness measuring device (manufactured by Toho Technology Corp., product name: TohoSpec3100). The results are shown in Table 1.

[0164] [Table 1]

[0165]

Claims

1. A grinding liquid comprising: abrasive grains, including cerium oxide; At least one aromatic carboxylic acid compound selected from the group consisting of aromatic carboxylic acids and salts thereof; and Halide ions.

2. The polishing liquid according to claim 1, wherein The halide ion includes at least one selected from the group consisting of fluoride ion, chloride ion, bromide ion, and iodide ion.

3. The polishing liquid according to claim 1, wherein The halide ions include iodide ions.

4. The polishing liquid according to claim 1, wherein The content of the halide ion is 0.01-5.0 mM.

5. The polishing liquid according to claim 1, wherein The aromatic carboxylic acid compound includes at least one selected from the group consisting of benzoic acid and salts thereof.

6. The polishing liquid according to claim 1, wherein The aromatic carboxylic acid compound includes at least one selected from the group consisting of mandelic acid and salts thereof.

7. The polishing liquid according to claim 1, wherein The content of the aromatic carboxylic acid compound is 0.01 to 1% by mass. The polishing liquid according to claim 1 , further comprising alkali metal ions.

9. The polishing liquid according to claim 1, further comprising nitrogen-containing cations.

10. The polishing liquid according to claim 9, wherein The nitrogen-containing cation includes at least one selected from the group consisting of ammonium ions and quaternary ammonium cations.

11. The polishing liquid according to claim 1, wherein The content of the abrasive grains is 0.1 to 5% by mass.

12. The polishing liquid according to claim 1, wherein The zeta potential of the abrasive particles is positive. The polishing liquid according to claim 1 , further comprising a cationic polymer.

14. The polishing liquid according to claim 13, wherein The cationic polymer includes a reactant of raw materials including at least dimethylamine and epichlorohydrin.

15. The polishing liquid according to claim 1, which has a pH of 2.00 to 5.

00.

16. A grinding method, wherein: A workpiece is polished using the polishing liquid according to any one of claims 1 to 15.

17. The grinding method according to claim 16, wherein: The polished part includes silicon oxide.

18. A method for manufacturing a part, wherein: A component is obtained by using the part to be ground by the grinding method according to claim 16.

19. A method for manufacturing a semiconductor component, wherein: A semiconductor component is obtained by using the member to be polished by the polishing method according to claim 16.